Procedures and Appeals Regarding the Public Procurement Contracts – Romanian Law - Tabacu , Andreea (Europejski Przegląd Prawa i Stosunków Międzynarodowych, 2025)
Public procurement, as the engine of a developing society, requires a series of jurisdictional procedures. These procedures are not just theoretical but have practical implications, guaranteeing compliance with the principles and rules of conducting the administrative procedures for awarding contracts and their development in accordance with the legal provisions. Romania has transposed Directive no. 665/89, making a distinction between the jurisdictional procedures in which the documents drawn up in the phase prior to the conclusion of the contract, directly related to the administrative award procedure and those aimed at the execution of contracts, their nullity, resolution, termination, which can be completed after the completion of the award procedure during the contract. Regardless of the situation, however, Romanian law gives concrete effects to the principle of celerity, which it protects through express rules that enshrine short terms for the procedure, for formulating some documents, for attacking the decision, although sometimes the same procedural provisions seem to affect this principle. The paper aims to present these provisions, interpreted especially in the light of celerity and the requirements of the supranational regulation, which are imposed in the internal procedures, including through the jurisprudence of the Court of Luxemburg. Zamówienia publiczne – jako motor rozwijającego się społeczeństwa – wymagają stosowania szeregu procedur jurysdykcyjnych. Procedury te nie są tylko teoretyczne, ale mają praktyczne implikacje, gwarantując zgodność z zasadami i regułami prowadzenia postępowań administracyjnych oraz ich rozwój oparty na przepisach prawa. Rumunia dokonała transpozycji dyrektywy nr 665/89, wprowadzając rozróżnienie między procedurami jurysdykcyjnymi, w których dokumenty sporządzane są na etapie poprzedzającym zawarcie umowy, bezpośrednio związanymi z administracyjną procedurą udzielania zamówień, a procedurami mającymi na celu wykonanie umów, ich unieważnienie, rozstrzygnięcie, rozwiązanie, które mogą zostać sfinalizowane po zakończeniu procedury udzielania zamówień w trakcie trwania umowy. Niezależnie jednak od sytuacji prawo rumuńskie nadaje konkretne skutki zasadzie szybkości, którą chroni poprzez wyraźne przepisy przewidujące krótkie terminy na przeprowadzenie procedury, sformułowanie niektórych dokumentów, zaskarżenie decyzji, chociaż czasami te same przepisy proceduralne wydają się wpływać na tę zasadę. Artykuł ma na celu przedstawienie tych przepisów, interpretowanych w szczególności w świetle szybkości i wymogów rozporządzenia ponadnarodowego, które są narzucane w procedurach wewnętrznych, w tym przez orzecznictwo Trybunału Luksemburskiego.